Control of carbonate sedimentation and reef growth in Llandovery sequences on the northwestern margin of the Yangtze Platform, south China - Yue, L; Kershaw, S; Xu, C (INT ASSOC GONDWANA RESEARCH, 2004)
The later Telychian (late Llandovery, Silurian) sea-level highstand was a suitable setting for global carbonate deposition and reef growth in epeiric seas. However, evidence from the northwest margin of Yangtze Platform indicates that small carbonate platforms developed in rapidly-subsiding small basins and were principally controlled by muddy clastic input. In particular, sediments of the Ningqiang Formation, late Telychian, usually more than 2000 m thick, are mostly shales, but eight major units of discontinuous (15 km maximum width) and relatively thin (120 m maximum thickness) reef-bearing carbonates, which developed when the sedimentation rate apparently lessened, occur within a relatively short time interval. This interval is between upper griestonensis to spiralis-grandis graptolite biozones, estimated as a c. 2 Ma duration. More than 30 small- to medium-scale patch reefs occur in several parts of the sequence, but only within the carbonate units. Shelly faunas common throughout the sequence reveal water depth to have been shallow during deposition of the Ningqiang Formation equivalent to BA2-3, which has a depth range from low intertidal to the base of the photic zone. BA3 is interpreted as being no more than 60 m deep (Boucot, 1975), which is above normal wave base, frequently affected by storms (Chen et al., 1996), and is regarded as optimum depth for high diversity of Silurian faunas (Boucot, 1975; Brett,1991). Thus, the rate of sediment accumulation kept pace with basement subsidence, and was a substantial factor for limiting reef growth. Sharp contacts between carbonate units and shales indicate that carbonate units are constrained by frequent inputs of terrigenous debris, as the major cause for termination of carbonate deposition. Therefore, carbonate platforms, and reefs they contained, formed during times when sediment input to the basin lessened and ended when it increased; present evidence does not allow correlation to modeled dry episodes, and we interpret the control to be principally ...